CODING THE IMMIGRANT EXPERIENCE: RACE, GENDER AND THE FIGURE OF THE DICTATOR IN JUNOT DIAZ'S OSCAR WAO. - SEPULVEDA, FREMIO (Journal of Caribbean Literatures)
A literary criticism of the novel "The Brief Wondrous Life of Oscar Wao," by Junot Diaz is presented. Topics include the novel's analogy of the position of a marginal and immigrant family to the dominant and normative Anglo-Saxon U.S. society, Diaz's position as a Dominican-American writer in a long tradition of diasporic Latino writing, and his use of other literary texts, particularly J.R.R. Tolkien's "Lord of the Rings" and Jack and Stan Lee's "Fantastic Four."